Blue AIE luminogens bearing methyl groups: different linkage position, different number of methyl groups, and different intramolecular conjugation. Issue 12 (26th October 2015) - Huang, Jing; Yang, Min; Yang, Jie; Tang, Runli; Ye, Shanghui; Li, Qianqian; Li, Zhen
Abstract : By changing the linkage position and linked number of the methyl group, the resultant AIE luminogens demonstrated adjustable intramolecular conjugation. Abstract : In this paper, four AIE-active luminogens (Methyl-BTPE, m MethylTPE- p TPE, o Methyl-BTPE and o MethylTPE- p TPE) exhibiting blue emissions were successfully synthesized, in which methyl groups of different numbers were introduced at different positions, to subtly tune the intramolecular conjugation. Their thermal, optical and electronic properties were fully investigated. The corresponding non-doped OLEDs exhibited high electroluminescence efficiencies with L max, η C, max, and η P, max values of up to 14 644 cd m −2, 4.06 cd A −1, and 9.7 lm W −1, respectively, showing the feasibility of this facile synthetic approach for the construction of blue AIE fluorophores.